1961
DOI: 10.1177/004051756103100901
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Reactions between Cotton Cellulose and Difunctional Epoxides

Abstract: Four diepoxides, namely, the diglycidyl ether of 1,4-butanediol, meso-butadiene diepoxide, Eponite 100, and vinylcyclohexene dioxide have been applied to cotton print cloth (80 X 80) from methanolic and aqueous solutions in the presence of zinc fluoborate as catalyst. Physical properties imparted to cotton by these diepoxides under various conditions of reaction and cure have been evaluated. Data are presented to show varia tion of fabric properties with mole ratios of diepoxide: Zn(BF4) 2: AGU ( anhydroglucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1961
1961
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The fabric employed was a desized, caustic-boiled and bleached 80 X 80 white cotton print cloth, 3.2 oz./yd.~ 2 Treatments, in general, were carried out as follows. A swatch of fabric was padded with a solution of the epoxide and curing agent to a wet pickup of about 8070.…”
Section: Methodsmentioning
confidence: 99%
“…The fabric employed was a desized, caustic-boiled and bleached 80 X 80 white cotton print cloth, 3.2 oz./yd.~ 2 Treatments, in general, were carried out as follows. A swatch of fabric was padded with a solution of the epoxide and curing agent to a wet pickup of about 8070.…”
Section: Methodsmentioning
confidence: 99%
“…Although reactions of cellulose and diglycidyl ethers had been intensively examined in the 1960s in the context of crease recovery of cotton clothing [14][15][16][17][18], no kinetic data on these reactions have been reported so far and comparison with literature values therefore turned out to be difficult. Nevertheless, the apparent activation energies found in this study are in good agreement with those reported by Rodrı ´guez et al [19] who investigated the cross-linking of cationic hydroxyethyl cellulose hydrogels with ethylene glycol diglycidyl ether, the monomeric homologue of PEGDE.…”
Section: Influence On Activation Energymentioning
confidence: 99%
“…Attempts were made to increase the nitrogen content of these cellulose exchangers by varying the mole ratios of reactants. Previously [3], for various diepox,ides. it was reported that for a,given epoxide: Zn ( 1%F4 > mole ratio, the add-on of various diepoxides increased as the anhydroglticose unit ( AGU ) : Zii(BF4 )1 mole ratio decreased.…”
Section: Introductionmentioning
confidence: 99%